On logarithmic Hölder continuity of mappings on the boundary - Sevost’yanov, Evgeny (Annales Fennici Mathematici, 2022)
We study mappings satisfying the so-called inverse Poletsky inequality. Under integrability of the corresponding majorant, it is proved that these mappings are logarithmic Hölder continuous in the neighborhood of the boundary points. In particular, the indicated properties hold for homeomorphisms whose inverse satisfy the weighted Poletsky inequality.